Identity Construction And Social Movements In Connection With Regional Head Elections In The Era Of Regional Autonomy - Hadiani Fitri (International Journal of Educational Technology and Society, 2024)
The construction of identity and social movements in the era of regional autonomy has a considerable influence on the regulations that exist in each region to administer their respective regions. Regional autonomy has brought several changes and progress to each region in improving prosperity. It is hoped that the implementation of autonomous regional government through direct regional head elections will provide opportunities for regions to channel their aspirations more freely. Regional Head Elections are suspected or assumed to be related to the rise of local culture or community in the form of identity politics. Identity politics is a tool of political struggle for an ethnic group to achieve certain goals. The phenomenon of a social movement of relative deprivation carried out in connection with the cancellation or postponement of regional head elections is the result of aspirations that have not been realized.